2011
DOI: 10.1016/j.bone.2011.09.040
|View full text |Cite
|
Sign up to set email alerts
|

In vivo loading increases mechanical properties of scaffold by affecting bone formation and bone resorption rates

Abstract: A successful bone tissue engineering strategy entails producing bone-scaffold constructs with adequate mechanical properties. Apart from the mechanical properties of the scaffold itself, the forming bone inside the scaffold also adds to the strength of the construct. In this study, we investigated the role of in vivo cyclic loading on mechanical properties of a bone scaffold. We implanted PLA/β-TCP scaffolds in the distal femur of six rats, applied external cyclic loading on the right leg, and kept the left le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 39 publications
(57 reference statements)
2
33
0
Order By: Relevance
“…Cahill et al found that models based on the designed scaffold geometry over-predicted the scaffold stiffness by up to 147% and that surface roughness is a factor that needs to be accounted for 4 . High resolution finite element meshes have been successfully generated from micro-CT scans giving accurate models of the real geometries of both bone tissue engineering scaffolds 6,10,38,49,50,52,57 and native bone tissue 2,29,40,47,51 .Micromechanics approaches to evaluate the mechanical properties of particle-reinforced composites traditionally use idealised microstructures based on particle distribution and are often modelled under periodic boundary conditions 5 . This approach was used by Eshragi et al to determine the bulk mechanical properties of a PCL/hydroxyapatite SLS scaffold 14 .…”
mentioning
confidence: 99%
“…Cahill et al found that models based on the designed scaffold geometry over-predicted the scaffold stiffness by up to 147% and that surface roughness is a factor that needs to be accounted for 4 . High resolution finite element meshes have been successfully generated from micro-CT scans giving accurate models of the real geometries of both bone tissue engineering scaffolds 6,10,38,49,50,52,57 and native bone tissue 2,29,40,47,51 .Micromechanics approaches to evaluate the mechanical properties of particle-reinforced composites traditionally use idealised microstructures based on particle distribution and are often modelled under periodic boundary conditions 5 . This approach was used by Eshragi et al to determine the bulk mechanical properties of a PCL/hydroxyapatite SLS scaffold 14 .…”
mentioning
confidence: 99%
“…By finding the mechanical stimulus, we design an animal study (Box 2) in which the loading condition in the animal is such that the level of mechanical stimulus in the scaffold is similar to that of the targeted clinical application. Bone formation over time inside the scaffold is obtained by longitudinal micro-CT imaging (Roshan-Ghias, Lambers, et al 2011). In addition, micro-CT imaging provides spatial information on the bone formation in the scaffold.…”
Section: Methodsmentioning
confidence: 99%
“…Results of the animal study with mechanical stimulus corresponding to that determined in Box 1 have been presented in Roshan-Ghias, Lambers, et al (2011). Briefly, the mechanical stimulation enhanced the bone formation inside the scaffold by 18% after 35 weeks.…”
Section: Boxes 2 Andmentioning
confidence: 99%
“…Similar methods were employed by Roshan-Ghias et al [13] to generate FE models of a scaffold-callus construct for uniaxial loading simulations. The use of four-point bending tests gives a more complete picture of the mechanical integrity of the scaffold-callus construct [6,11] under the complex loading conditions in-vivo [14] in comparison to the use of uniaxial loading alone.…”
Section: Introductionmentioning
confidence: 99%